Extracellular Vesicles Produced by the Gram-positive Bacterium Bacillus subtilis are Disrupted by the Lipopeptide Surfactin - Brown, Lisa (2014)
Previously, extracellular vesicle production in Gram-positive bacteria was dismissed due to the absence of an outer membrane, where Gram-negative vesicles originate, and the difficulty in envisioning how such a process could occur through the cell wall. However, recent work has shown that Gram-positive bacteria produce extracellular vesicles and that the vesicles are biologically active. In this study, we show that Bacillus subtilis produces extracellular vesicles similar in size and morphology to other bacteria, characterized vesicles using a variety of techniques, provide evidence that these vesicles are actively produced by cells, show differences in vesicle production between strains, and identified a mechanism for such differences based on vesicle disruption. We found that in wild strains of B. subtilis, surfactin disrupted vesicles while in laboratory strains harboring a mutation in the gene sfp, vesicles accumulated in the culture supernatant. Surfactin not only lysed B. subtilis vesicles, but also vesicles from Bacillus anthracis, indicating a mechanism that crossed species boundaries. To our knowledge, this is the first time a gene and a mechanism has been identified in the active disruption of extracellular vesicles and subsequent release of vesicular cargo in Gram-positive bacteria. We also identify a new mechanism of action for surfactin.